Analysis of terpenoids and their gene regulatory networks on the basis of the transcriptome and metabolome of Opisthopappus longilobus - Liu, Hua; Chai, Yuhong; Chen, Haixia; Chen, Wendan; Li, Yushu; Liu, Wenchao; Guo, Shuang; Sun, Lei; Zhou, Xiumei; Huang, Conglin; Tang, Xiaowei; Luo, Chang; et al. (Frontiers in Plant Science, 2022)
Opisthopappus longilobus, which is a unique wild plant resource in China, produces leaves and flowers with distinct aromas. However, there have been relatively few molecular studies on its floral aroma, which has hindered the research on this plant species at the molecular level and the breeding of novel varieties. In this study, transcriptome and metabolome analyses were performed using O. longilobus leaves, buds, and inflorescences at the exposure, initial opening, and blooming stages. Using high-quality reads and assembly software, a total of 45,674 unigenes were annotated according to the Nr, Swiss-Prot, KOG, and KEGG databases. Additionally, a GC-MS system and a self-built database were used to detect 1,371 metabolites in the leaves, buds, and inflorescences. Terpene metabolites were the most common compounds (308 in total). We analyzed the gene network regulating terpenoid accumulation in O. longilobus and identified 56 candidate genes related to terpenoid synthesis. The expression of OlPMK2, OlMVK1, OlTPS1, and OlTPS3 may lead to the accumulation of 11 different terpenoids specifically in the inflorescences at the exposure, initial opening, and blooming stages. The generated data may be useful for future research on O. longilobus genetic resources and the molecular mechanism regulating aroma formation in this plant species. The findings of this study may be used to accelerate the breeding of new O. longilobus varieties with enhanced aromatic traits.